Catecholamine, blood lactate and ventilatory responses to multi-cycle-run blocks - Hue, O.; Le Gallais, D.; Boussana, A.; Galy, O.; Chamari, K.; Mercier, B.; Prefaut, C. (Medicine & Science in Sports & Exercise, 2000)
Purpose and Methods: This study was designed to determine whether the physiological responses elicited during the run part of repeated bouts of cycle-run exercise are similar to those required during the run segment of a cycle-run succession. Thirteen male triathletes underwent four successive laboratory trials: 1) an incremental treadmill test, 2) an incremental cycle test, 3) 30 min of cycling followed by 20 min of running (C-R), and 4) five repeated bouts of 6 min of cycling and 4 min of running (X-CR). During the C-R and X-CR trials, venous blood samples were obtained to measure lactate, epinephrine and norepinephrine concentrations. During all trials, ventilatory data were collected every min using an automated breath-by-breath system. Results: The results showed that 1) the cardiorespiratory responses observed during running were similar in the X-CR and C-R trials, 2) the lactate concentration was similar in both trials, 3) the epinephrine concentration was greater (277.9± 11.9 vs 169.8 ± 86.7 pg.mL-1, P < 0.025) in X-CR than in C-R, and 4) the norepinephrine concentration was similar in both trials, except at the first cycle-run succession (T1) of X-CR. Conclusion: We concluded that 1) multi-block training is a good method to stimulate the specific adaptations required for the cycle-run succession, and particularly for the cycle-run transition, and 2) multi-block training seems to induce a greater catecholaminergic response, which may be due to a combination of an inherent effect of this type of training and the triathletes' relative lack of experience with it. In any case, the efficacy of the multi-block model needs to be more thoroughly evaluated over the course of a longer-term training program.